2016
DOI: 10.1007/s00280-016-3076-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a method for calculating carboplatin dosage in DeVIC ± R therapy (combination therapy of dexamethasone, etoposide, ifosfamide and carboplatin with or without rituximab) as a salvage therapy in patients with relapsed or refractory non-Hodgkin lymphoma

Abstract: PurposeSeveral studies have evaluated the utility of extrapolating the Calvert formula in calculating carboplatin (CBDCA) dosages in solid tumours; however, data regarding haematological cancers are less. Therefore, we conducted a preliminary study of the utility of extrapolating the Calvert formula in calculating CBDCA dosages for DeVIC ± R therapy.MethodsA retrospective study on 57 non-Hodgkin lymphoma patients who had received DeVIC ± R therapy was conducted. The area under the curve (AUC) of CBDCA was back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although this study indicated the usefulness of a dosing design of CBDCA considering renal function for the incidence of thrombocytopenia in DeVIC ± R therapy, but because this study was based on the first course only, the efficacy of the treatment could not be evaluated because this study examined the data in the first course only. Tomono et al reported that an AUC of 4 or higher for CBDCA improves therapeutic efficacy but did not assess the upper limit of the AUC (Tomono et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study indicated the usefulness of a dosing design of CBDCA considering renal function for the incidence of thrombocytopenia in DeVIC ± R therapy, but because this study was based on the first course only, the efficacy of the treatment could not be evaluated because this study examined the data in the first course only. Tomono et al reported that an AUC of 4 or higher for CBDCA improves therapeutic efficacy but did not assess the upper limit of the AUC (Tomono et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In each case, the CBDCA dosing design is based on the Calvert formula; however, the CBDCA dosing design in DeVIC therapy (21-day cycles of DEX, VP-16, IFO, and CBDCA) uses the body surface area method (300 mg/m 2 ), (Okamoto et al, 1994) and no prospective clinical trials have been reported using the AUC and Calvert formula for the CBDCA dosing design. In a retrospective study, Tomono et al reported that while an AUC of 4 or more for CBDCA improved therapeutic efficacy, it increased the incidence of thrombocytopenia and neutropenia (Tomono et al, 2016).…”
Section: Research Articlementioning
confidence: 99%
“…In previous studies in non‐squamous NSCLC, combination therapy of carboplatin and pemetrexed as a first‐line treatment has an excellent safety profile and a convenient administration schedule . A retrospective study in non‐Hodgkin lymphoma patients, DeVIC ± R therapy (combination therapy of dexamethasone, etoposide, ifosfamide, and carboplatin with or without rituximab) yielded a significantly higher overall response rate (ORR) for the area under the curve (AUC) ≥4 than for AUC <4, and the frequency of grade ≥3 decreased platelet and neutrophil counts occurred at higher rates for AUC ≥4 . However, in another study of small cell lung cancer patients, no significant difference in ORR (ORR 69.2% vs. 71.4%) and overall survival (median 10.0 vs. 12.0 months) were observed between the AUC ≤5 and >5 groups for carboplatin plus etoposide treatment .…”
Section: Introductionmentioning
confidence: 99%